The Impact of Intangible Resources and Dynamic Capability’s Factors on Business Performance in the Mediation of Innovation Capability: A Case Study of Tourism Companies in Ho Chi Minh City, Vietnam - Dan Van Phan, Tam Minh Huynh (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Purpose: This study investigates the impact of intangible resource’s and dynamic capability’s factors on business performance in the mediation of innovation capability in tourism companies in Ho Chi Minh City, Vietnam. Design/Methodology/Approach: Impact of intangible resource’s and dynamic capability’s factors on business performance in the mediation of innovation capability was confirmed by 535 managers who operated directly tourism companies applying the CB-SEM estimation method. Findings: The results shows that both intangible resource’s factors and dynamic capability’s factors have impacted on business performance via the mediation of innovation capability. Conclusion: Business performance and innovation capability are directly impacted by both intangible resource’s factors and dynamic capability’s factors. Besides there also confirmed the mediating role of innovation capablity towards the relationship between intangible resource’s factors and dynamic capability’s factors and business performance. Practical Implications: The study’s investigation has implications for both managers when build performance oriented strategics for their company. Limitations: this study has been examined in Ho Chi Minh City – Vietnam; there, there could impact the generalization in research scope. Contribution to literature: This study focuses to examine the impact of the second-order scale of intangible resource and dynamics capability on business performance in the mediation of innovation capability that previous studies haven’t still referred yet.